Planejamento estratégico: a aplicação dessa ferramenta administrativa na empresa de um ponto de vista ético - Ferreira, Edson Alves (2012)
The survey was conducted in order to show what happens to organizations that make a proposal in its strategic planning and, in practice are different, in other words, the vision and mission are only exposed decorative, that in some situations are exposed somewhere in the organization. In the observation made, it was found, between exposure and implementation of the proposed planning there is a long way to go. I imagine that this distance exists precisely because of the difficulty of implanting, these difficulties are prevalent because of the so-called comfort zone where people are. A change is required before this difficulty. Another point that often interferes with the planning is ethical model to be use. This ethical perspective for planning seems still in its infancy. It is remarkable the importance of strategic planning in the management of any organization, but most often is used only in large corporations. Again it's possible can see the power of capital, capital that this is not always harmful. Only the thought of more egalitarian society has thought of it, it s again dominating the capital, because small business in the the majority cases cannot afford for this deployment. Moreover, beyond them take control of capital, there's the ethical problem. What might be called the ethical problem? It would be entrepreneurs with little preparation of these behaviors in society. In summary, small companies, whose management process is almost always familiar, becomes even more difficult this deployment. Therefore, this observation showed that some companies do strategic planning on paper and only expose your banner with the phrase Main planning.